Identification of SMG3, a QTL Coordinately Controls Grain Size, Grain Number per Panicle, and Grain Weight in Rice - Li, Ruosi; Li, Zhen; Ye, Jing; Yang, Yingying; Ye, Juahua; Xu, Siliang; Liu, Junrong; Yuan, Xiaoping; Wang, Yiping; Zhang, Mengchen; Yu, Hanyong; Xu, Qun; et al. (Frontiers in Plant Science, 2022)
Grain size, grain number per panicle, and grain weight are key agronomic traits that determine grain yield in rice. However, the molecular mechanisms coordinately controlling these traits remain largely unknown. In this study, we identified a major QTL, SMG3, that is responsible for grain size, grain number per panicle, and grain weight in rice, which encodes a MYB-like protein. The SMG3 allele from M494 causes an increase in the number of grains per panicle but produces smaller grain size and thousand grain weight. The SMG3 is constitutively expressed in various organs in rice, and the SMG3 protein is located in the nucleus. Microscopy analysis shows that SMG3 mainly produces long grains by increasing in both cell length and cell number in the length direction, which thus enhances grain weight by promoting cell expansion and cell proliferation. Overexpression of SMG3 in rice produces a phenotype with more grains but reduces grain length and weight. Our results reveal that SMG3 plays an important role in the coordinated regulation of grain size, grain number per panicle, and grain weight, providing a new insight into synergistical modification on the grain appearance quality, grain number per panicle, and grain weight in rice.